Create, build and manage online brands for internet companies - Bilro, R.; Loureiro, S. (Proceedings of the 7th Annual Conference of the EuroMed Academy of Business, 2014)
Research Aims The primary objective of this ongoing research is to identify the main assets that create brand success for internet-only companies. Based on an extensive and systematic literature review, this study seeks to identify the constructs who drive online brands for a successful life. Eighteen articles were identified and from those some preliminary reflections were taken.